Dipole Molecule-Mediated Modulating Residual PbI 2 Clusters in Two-Step-Processing Inverted Perovskite Photovoltaics - Wang, Chenyun; Qu, Duo; Han, Ruilin; Zhang, Xinyue; Shang, Chuanzhen; Zhou, Bin; Wang, Shasha; Hu, Hanwei; Zhao, Wenying; Qin, Qichao; Zhang, Yajie; Guo, Qiang; et al. (Nano letters, 2024)
The precise modulation of PbI presence is of paramount importance in the domain of perovskite solar cell fabrication, particularly when employing the two-step method. The distinct crystallization trajectory inherent to this method often leaves unreacted PbI at the buried interface, which can create a large number of defect states. To address this challenge, we have introduced a strategic predeposition of the dipole molecule, 3-(decyldimethylammonio)propane sulfonate inner salt (3DPSI). This intervention serves to regulate residual PbI clusters and quash the emergence of associated derivative defects, such as Pb , V , and V . Through a synergistic approach combining experimental precision with theoretical rigor, we gained profound insights into the enhancement of crystal quality and the effective suppression of defects. The predeposition of the dipole molecule has yielded a remarkable power conversion efficiency of 24.62% in two-step-processing inverted perovskite photovoltaics and significantly improved the stability under continuous illumination.